Retrospective Analysis of Pattern of Poisoning in Uttarakhand - Saxena, V; Atal, DK; Das , S (Journal of Indian Academy of Forensic Medicine, 2014)
Poisoning cases are important part of medico-legal cases coming to a heath care centre. This paper presents the study of cases of poisoning received in the casualty of Himalayan Institute of Medical Sciences, Dehradun during a span of 2 years (2011-2012). The cases were then analysed on various epidemiological parameters, feeding the information in the predesigned Performa prepared for this purpose. It was concluded that there is not much gender difference, however, majority of victims were married and most commonly among people from the age group of 21-30 years. Maximum number of cases took place in the month of November and May. During the span of the study, poisoning due to insecticide were predominant, constituting about 57 percent of all poisoning cases, while poisoning through unknown compounds was the second most common fatal poisoning.